2010
DOI: 10.1109/lawp.2010.2051311
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial-Inspired, Electrically Small Huygens Sources

Abstract: Electrically small electric and magnetic dipole antennas are introduced that are based on electric and magnetic near-field resonant parasitic (NFRP) elements that are electrically coupled to the driven element. By properly combining these two NFRP antenna types, electrically small Huygens sources are realized. The proposed Huygens sources have one feed point, are well matched to 50 , and have high radiation efficiencies.Their predicted directivity patterns approach the known Huygens source theoretical limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 14 publications
7
105
0
1
Order By: Relevance
“…The increasing demand of wireless device miniaturization for communication and sensor applications, and the search of new materials with electromagnetic properties 'à la carte', has fostered a renewed interest in subwavelength particles as basic building blocks for controlling optical radiation at subwavelength scales. These issues underline the emerging concepts of metamaterial inspired microwave and radio-wave electrically small antennas 4 and their optical analogues, either dielectric 5,6 or based on plasmon subwavelength optics 7 .…”
mentioning
confidence: 99%
“…The increasing demand of wireless device miniaturization for communication and sensor applications, and the search of new materials with electromagnetic properties 'à la carte', has fostered a renewed interest in subwavelength particles as basic building blocks for controlling optical radiation at subwavelength scales. These issues underline the emerging concepts of metamaterial inspired microwave and radio-wave electrically small antennas 4 and their optical analogues, either dielectric 5,6 or based on plasmon subwavelength optics 7 .…”
mentioning
confidence: 99%
“…To outline the design methodology, a reflectionless Huygens' surface that provides a spatially varying phase response is experimentally demonstrated at microwave frequencies. This structure can be envisaged as a nonperiodic distribution of Huygens' sources [13,14].…”
mentioning
confidence: 99%
“…On the other hand, recent designs have suggested that Huygens sources may be advantageous, particularly in regards to their FTBR values [20][21][22][23][24][25]. Consequently, it was explored whether or not the magnetic-based EZ antenna could be augmented with an electric-based NFRP antenna to achieve an electrically small Huygens source.…”
Section: D Magnetic Ez Antennamentioning
confidence: 99%
“…These include, for example, end-fire arrays [5][6][7][8], electromagnetic band-gap (EBG) structures [9], high impedance surfaces and artificial magnetic conductors [10][11][12][13], nearfield resonant parasitic (NFRP) elements [14][15][16], nonFoster circuit-augmented antennas [17], two-element NFRP antenna arrays [18,19], and Huygens sources [20][21][22][23][24][25]. The metamaterial-inspired NFRP antenna designs have led to the realization of many performance enhancements of compact systems.…”
Section: Introductionmentioning
confidence: 99%